Effects of Heating Therapy on Pain, Anxiety, Physiologic Measures, and Satisfaction in Patients Undergoing Cystoscopy - Oh Suk Kwon; Bokyeong Kwon; Jihye Kim; Bo-Hwan Kim (Elsevier, 2022)
SUMMARY: Purpose: Cystoscopy is the most common procedure used to diagnose urological diseases; however, it is invasive and can be associated with pain and anxiety. Although pain relieving medications, such as lidocaine lubricants, are used during cystoscopy, the procedure still causes discomfort. Therefore, non-medical intervention is needed to reduce pain and anxiety during the procedure and increase patient satisfaction. The aim of this study was to evaluate the effect of heating therapy on pain, anxiety, physiologic measures, and satisfaction during cystoscopy. Methods: This was a single-blinded, single-center, randomized controlled trial. A total of 145 participants who underwent cystoscopy between August 2017 and October 2017 were recruited and randomly assigned to an experimental or control group. Before and after cystoscopy, all the participants self-reported the degree of pain they felt, while pain was objectively assessed by trained nurses. Anxiety was evaluated using the validated Korean version of the State-Trait Anxiety Inventory. Blood pressure and pulse rate were also recorded as physiologic measures. After cystoscopy, satisfaction was measured in the experimental group only using the Korean version of the Client Satisfaction Questionnaire. Results: Heating therapy reduced both subjective and objective pain and anxiety in the experimental group compared to the control group. Heating therapy also decreased the systolic and diastolic blood pressure and pulse rate in the experimental group compared to the control group. Women reported significantly greater satisfaction than men. Conclusion: Heating therapy during cystoscopy is a convenient and effective nursing intervention that decreases pain and anxiety and enhances patient satisfaction.The study has been registered with the Clinical Research Information Service Registry, and the trial registration number is [12616000803493].